Dysfunctional uterine bleeding: ormeloxifene versus combined oral contraceptive pills - Luthra, Sonia; Dwivedi, A. D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Dysfunctional uterine bleeding is abnormal bleeding that occurs in the absence of recognizable pelvic pathology, general medical disease, or pregnancy. Globally, health care systems are focusing on low morbidity and low cost therapeutic interventions. Hence, medical treatment for DUB is high on the priority list. This comparative study was conducted to analyse the efficacy of ormeloxifene and combined oral contraceptive pills in reducing the blood loss and endometrial thickness in cases of DUB. Methods: This prospective study was conducted on women with dysfunctional uterine bleeding, who attended Gynaecology OPD at Hind Institute of Medical Sciences, between August 2015 and April 2016. After applying inclusion and exclusion criteria, 72 women diagnosed with DUB were enrolled randomly in two groups A and B. Group A was treated by Ormeloxifene and Group B patients were treated with combined oral contraceptive pills for three consecutive cycles. The efficacies of the studied drugs were compared by analyzing the mean change in the pre and post treatment PBAC score, haemoglobin level and endometrial thickness using unpaired t-test. Results: Ormeloxifene was found to be significantly more effective (p <0.0001) than OCPs in controlling the menstrual blood loss (79% reduction in group A Vs 55.5% reduction in group B). Reduction in endometrial thickness was also more in the group receiving Ormrloxifene, however this was statistically not significant (p = 0.19). No major side effect observed with the use of Ormeloxifene. Conclusions: Ormeloxifene can be an effective and safe therapy in the treatment of Dysfunctional uterine bleeding.